A Reader in International Corporate Finance, Volume Two - Claessens, Stijn; Laeven, Luc (Washington, DC: World Bank, 2012)
The Reader in International Corporate Finance offers an overview of current thinking on six topics: law and finance, corporate governance, banking, capital markets, capital structure and financing constraints, and the political economy of finance. This collection of 23 of the most influential articles published in the period 2000-2006 reflects two new trends: 1) interest in international aspects of corporate finance, particularly specific to emerging markets, and 2) awareness of the importance of institutions in explaining global differences in corporate finance.